2009
DOI: 10.1007/s11434-009-0471-1
|View full text |Cite
|
Sign up to set email alerts
|

Electric field soundings and the charge structure within an isolated thunderstorm

Abstract: A strong electric (E) field sounding system was designed to measure the vertical component of the E-fields, temperature, relative humidity and GPS data along the sounding path. In the summer of 2008, in situ measurements of E-field inside the thunderstorms were conducted in Pingliang, Gansu Provience, with the cooperation of an X-band weather radar. One E-field profile inside a thunderstorm was successfully acquired. The sounding data indicated four charge layers along the sounding trajectory, three inside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The observations showed that three charge regions existed in the cloud and the negative charge region stayed in the middle part of the cloud. An obvious feature of the charge structure was that each charge region located at a lower altitude when compared with those observed in the mature stage (Zhao et al, 2010). On the one hand, the cloud upper boundary was limited to 6.3 km; on the other hand, the predominant airflow in this stage was a downdraft.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The observations showed that three charge regions existed in the cloud and the negative charge region stayed in the middle part of the cloud. An obvious feature of the charge structure was that each charge region located at a lower altitude when compared with those observed in the mature stage (Zhao et al, 2010). On the one hand, the cloud upper boundary was limited to 6.3 km; on the other hand, the predominant airflow in this stage was a downdraft.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Secondly, the charging process may not have ceased completely and no lightning flash occurred to consume the charge in the cloud. Zhao et al (2010) found that a thunderstorm in the Pingliang region had four charge regions in the mature stage, alternating in polarity, i.e., an upper positive charge region, a middle negative charge, a lower positive charge center and a negative screening charge layer at the bottom. These results support our observation that the charge structure in the mature stage was not substantially different from that in the decay stage before dissipation of the charge region.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observations in the same area have also confirmed the tripole structure in thunderstorms and have provided evidence for the existence of an upper positive charge center (UPCC; Zhang et al, ). In Pingliang (about 1,400 m ASL), another area on the northeastern edge of the Tibetan Plateau, a tripole structure with a large LPCC, was also observed through electric sounding measurements of an isolated thunderstorm (Zhao et al, ).…”
Section: Introductionmentioning
confidence: 92%
“…These lightnings occur in the troposphere and have been extensively studied [1][2][3][4][5][6][7][8][9][10][11]. However, there are another type of lightning discharges which occur above the thunderstorms, with the top altitude even reaching the ionosphere.…”
mentioning
confidence: 99%